2018
DOI: 10.5455/ijmsph.2018.1130015122017
|View full text |Cite
|
Sign up to set email alerts
|

How to adjust the strategy of radiopathologic teaching to achieve the learning outcomes?

Abstract: INTRODUCTIONDevelopment of our radiopathology curriculum of Faculty of Medicine, Albaha University (FMBU), had been finished and implemented 7 years ago. During this period, many questions have been called to mind, of these: Does our radiopathology curriculum esteem students' learning style? Background:The integrated-based education must pay attention to the beneficiaries, in whom our learning outcomes would be achieved. For establishing any curriculum for integrated-based medical schools, one must be aware wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…These suggestions include clarification of learning objectives, periodic tutor driven discussions with students, the formation of small groups, panel discussions with the students about SDL themes, and identification of student learning styles. 35 – 37 These suggestions have been implemented in courses with good results.…”
Section: Discussionmentioning
confidence: 99%
“…These suggestions include clarification of learning objectives, periodic tutor driven discussions with students, the formation of small groups, panel discussions with the students about SDL themes, and identification of student learning styles. 35 – 37 These suggestions have been implemented in courses with good results.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Few studies have also recommended that the facilitator need to encourage and promote the students for their active participation in SDL. [28][29][30][31][32] these authors also concluded that such exercises help in acquiring and improving clinical skills. Researchers also found that SDL can be effectively inculcated in the current curriculum if it is properly framed with desired outcomes at each stage or phase of the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was composed of both qualitative and quantitative components. The qualitative items were scored on a Likert scale of one to five according to the level of satisfaction (11)(12)(13)(14). In the qualitative component, the respondents were required to write comments about various features of the integrated curriculum in terms of its strengths and limitations.…”
Section: Methodsmentioning
confidence: 99%
“…In response to some of the drawbacks that emerged through an investigative periodic curricular evaluation at different medical schools including Albaha School of Medicine (ABSM) (10)(11)(12)(13), an improvement action plan was created to provide a solution to these limitations. The first step is to identify the major issues that interfere with curriculum implementation especially in the newly integrated medical schools.…”
Section: Introductionmentioning
confidence: 99%